2016
DOI: 10.3390/ijerph13121196
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality Strategies on Public Health and Health Equity in Europe—A Systematic Review

Abstract: Air pollution is an important public health problem in Europe and there is evidence that it exacerbates health inequities. This calls for effective strategies and targeted interventions. In this study, we conducted a systematic review to evaluate the effectiveness of strategies relating to air pollution control on public health and health equity in Europe. Three databases, Web of Science, PubMed, and Trials Register of Promoting Health Interventions (TRoPHI), were searched for scientific publications investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 46 publications
0
39
0
7
Order By: Relevance
“…Few studies have evaluated the health inequality impacts of air quality strategies, and inconsistent results indicate that beneficial effects cannot be presumed. (Wang et al, )…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have evaluated the health inequality impacts of air quality strategies, and inconsistent results indicate that beneficial effects cannot be presumed. (Wang et al, )…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have evaluated the health inequality impacts of air quality strategies, and inconsistent results indicate that beneficial effects cannot be presumed. (Wang et al, 2016) The West Yorkshire zone was identified as having the fourth most significant NO 2 concentration issues in the United Kingdom, with exposure concentrated in deprived inner-city areas. Exposure to atmospheric particles smaller than 2.5 μm (PM 2.5 ) was estimated to be responsible for 1 in 20 deaths in the area, and a health impact assessment showed that efforts to reduce this mortality would produce the largest benefits in the most deprived areas (Cooper, Lomas, Jones, Crowther, & Gent, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Effective control of traffic-related air pollution requires national action, supplemented by action by local authorities, as well as public health and healthcare professionals, employers in all sectors, and the public (Wang et al 2016). To address the need for evidence based measures, the National Institute for Health and Care Excellence (NICE), jointly with Public Health England (PHE), have published a guideline on the effectiveness of local interventions aiming to reduce emissions, ambient concentration levels and personal exposure to road-traffic-related air pollution (NICE 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Shandas et al [74] have made use of spatial analysis to understand the community structure, population distribution, and air quality at the neighbor- A systematic review of 15 recent publications resulted in four strategies to improve urban air quality: general regulations on air emissions, road traffic related interventions, energy generation related interventions, and greenhouse gas emission reduction interventions [92]. Particulate matter and nitrogen dioxide were the pollutants of greatest concern in these 15 papers.…”
Section: Other Ways To Improve Air Qualitymentioning
confidence: 99%
“…The establishment of low emission zones and congestion charging schemes have been successful in reducing PM2.5 and nitrogen dioxide concentrations in the areas of the cities where they have been implemented. More than 200 low emission zones have been implemented in Europe [92]. Regulations that encourage electric vehicle purchase and use in cities improve air quality and reduce greenhouse gas emissions.…”
Section: Other Ways To Improve Air Qualitymentioning
confidence: 99%